The Enlightened Capitalist - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2014)
On April 16, 2014, we published a short article in the Indian fortnightly Frontline, titled 'Profit from Crisis'. Scarcely had a day passed from the article's publication that we got an angry email from an asset manager whom we'll call 'Mr. X'. Mr. X is an enlightened capitalist, and reading our piece had set him on fire. Our article, he protested, was 'terribly flawed'. It 'failed miserably' in understanding capitalism, and its allegation that capitalists do not want recovery is doing 'tremendous harm'. This note deconstructs Mr. X's protestations in the context of the current capitalist angst.
Keywords: 330; beating the average; environment; real capitalism; sabotage; statism